Load voltage-based MPPT technique for standalone PV systems using adaptive step - Kumar V.; Ghosh S.; Naidu N.K.S.; Kamal S.; Saket R.K.; Nagar S.K. (My University, 2025)
This paper presents a load voltage based (LVB) maximum power point tracking (MPPT) technique using adaptive step-size (ASS) for standalone photovoltaic (PV) systems. The technique improves the convergence speed of the MPPT using a single voltage sensor to measure the load voltage (VL) regardless of the nature of load type. The ASS of the MPPT controller is varied according to the slope [Formula presented] of VL versus duty ratio (D) characteristic. The effectiveness of the proposed technique is tested for different insolation level conditions. This ASS based control scheme improves the convergence performance over fixed step-size (FSS) scheme under varying insolation condition. A single-ended primary inductance converter (SEPIC) is used for interfacing the PV system with the resistive load, which increases the operating range of the PV system. The tracking performance of the proposed technique is compared with FSS MPPT, perturb and observe (P&O) and incremental-conductance (IncCond) techniques by simulation. Experimental verification using a developed laboratory prototype is also carried out. © 2020 Elsevier Ltd